PERAN TEKNOLOGI KOMUNIKASI DALAM MENINGKATKAN EFEKTIVITAS PEMASARAN DIGITAL PADA GENERASI Z - Engelbert, Sheron Mariana Alezandra (Sintesa, 2025)
The transformation of communication technology has significantly altered digital marketing strategies, particularly in targeting Generation Z, known as "digital natives." This generation exhibits unique characteristics, such as a preference for engaging visual content, personalized approaches, and support for brands prioritizing sustainability and social values. As consumers raised in the digital era, Generation Z leverages social media platforms like Instagram, TikTok, and YouTube not only for entertainment but also to seek information and make transactions. This study examines the role of modern communication technologies, including artificial intelligence (AI), data analytics, and marketing automation, in shaping effective strategies for Generation Z. Findings reveal that technological advances play a major role in shaping society, including the way humans communicate and adapt. Additionally, sustainability and brand authenticity are crucial in fostering consumer loyalty. Generation Z supports brands that openly commit to transparent, environmentally friendly, and ethical practices. The role of AI, such as chatbots and predictive analytics, is also significant in enhancing consumer experiences by offering responsive interactions and relevant personalization. The conclusion of this study emphasizes the importance of technological innovation in digital marketing strategies so as to create a profitable thing in the form of a stronger and sustainable relationship with Generation Z. Companies that are able to integrate technology, sustainability, and personalization in their approach will have a competitive advantage so that changes are created in the form of a growing market. Keywords: Generation Z; Digital Marketing; Communication Technology; Personalization; Sustainability